A virtual repository approach to departmental information sharing - Jamaludin, Zulikha; Wan Ishak, Wan Hussain (2010)
Realising the difficulties in information sharing among the academicians, this paper introduces an alternative information sharing model supporting information management features. The model is designed in an attempt to facilitate information distribution and information sharing at minimum effort and cost. A centralised database approach is used in the model enabling any educator in the higher learning institution to participate and manage the database, conceptualizing that the database is their very own ‘personal library’. This model is then implemented in an application given a persona name ViRepo –-a web-based internal virtual repository. The process of analysing, designing, and implementing the model into ViRepo is sufficiently reported in this paper. ViRepo proved that the model, in actual fact, allows information access, information sharing, information management, partnership enhancement, and allows an utmost repository control by each and every participating educator.